2015
DOI: 10.1038/srep14648
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic weight bearing is an efficient and predictable method for evaluation of arthritic nociception and its pathophysiological mechanisms in mice

Abstract: The assessment of articular nociception in experimental animals is a challenge because available methods are limited and subject to investigator influence. In an attempt to solve this problem, the purpose of this study was to establish the use of dynamic weight bearing (DWB) as a new device for evaluating joint nociception in an experimental model of antigen-induced arthritis (AIA) in mice. AIA was induced in Balb/c and C57BL/6 mice, and joint nociception was evaluated by DWB. Western Blotting and real-time PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…The presence of TNF in peripheral and central structures is fundamental for joint pain in arthritis (6,14,27,44). During joint inflammation in experimental models of arthritis, up-regulated TNF in the spinal cord is implicated in increased articular nociception (27,54). Quadros et al (27) demonstrated that challenging the joints of immunized mice with a high dose of mBSA produce marked articular hypernociception that is associated with increased TNF expression and microglial activation in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of TNF in peripheral and central structures is fundamental for joint pain in arthritis (6,14,27,44). During joint inflammation in experimental models of arthritis, up-regulated TNF in the spinal cord is implicated in increased articular nociception (27,54). Quadros et al (27) demonstrated that challenging the joints of immunized mice with a high dose of mBSA produce marked articular hypernociception that is associated with increased TNF expression and microglial activation in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…TNF, a pro-nociceptive cytokine, is directly involved in various pain disorders, including joint pain in different forms of arthritis, due to central and peripheral actions (6,27). However, without conditional peripheral inflammation, TNF has not been shown to elicit persistent pain in arthritis.…”
Section: Prolonged Joint Nociception Is Dependent On Tnf In the Sensomentioning
confidence: 99%
See 1 more Smart Citation
“…This test reports parameters including weight, surface area, and time spent on each paw, along with the variability of these measures. The Dynamic Weight Bearing Test has been used in medial meniscus transection and adjuvant induced arthritis studies, finding reduced weight placed on the injured limb in both models 38, 44, 45 .…”
Section: Kinetic Gait Parametersmentioning
confidence: 99%
“…Mice were immunized as previously described (9,10,11). Briefly, the mice were sensitized with 500 ug of mBSA in 0.2 mL of an emulsion containing 0.1 mL of saline and 0.1 mL of Freund's Complete Adjuvant (CFA) (1 mg/mL of inactive Mycobacterium tuberculosis), administered by subcutaneous (s.c.) injection on day 0.…”
Section: Induction Of Antigen-induced Arthritis (Aia)mentioning
confidence: 99%